2001
DOI: 10.1089/10507250152484592
|View full text |Cite
|
Sign up to set email alerts
|

Management Practices Among Primary Care Physicians and Thyroid Specialists in the Care of Hypothyroid Patients

Abstract: Prospective studies are not available to address various issues commonly encountered in the management of hypothyroid patients. We have conducted a case-based mail survey of American Thyroid Association (ATA) members and primary care providers (PCP) regarding hypothyroidism management issues. A majority of ATA members and a minority of PCPs used antithyroid antibody testing in the evaluation of hypothyroidism. Approximately 2/3 of all respondents indicated that they would treat patients with mild thyroid failu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
2
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 44 publications
2
21
2
4
Order By: Relevance
“…In general, the response rates were higher in countries where the survey was forwarded to GPs affiliated with a research and teaching network. Although the overall response rate in this study was comparable to a case-based survey on subclinical hypothyroidism among primary care physicians in the US, 20 the low response impaired generalisability and prohibited performing a paired analysis. However, sensitivity analyses using only data from the Netherlands, Germany, and Switzerland showed similar results as when using data from all countries.…”
Section: Strengths and Limitationsmentioning
confidence: 75%
See 2 more Smart Citations
“…In general, the response rates were higher in countries where the survey was forwarded to GPs affiliated with a research and teaching network. Although the overall response rate in this study was comparable to a case-based survey on subclinical hypothyroidism among primary care physicians in the US, 20 the low response impaired generalisability and prohibited performing a paired analysis. However, sensitivity analyses using only data from the Netherlands, Germany, and Switzerland showed similar results as when using data from all countries.…”
Section: Strengths and Limitationsmentioning
confidence: 75%
“…These findings are in line with a previous case-based survey among primary care physicians and thyroid specialists in the US in which physicians adopted a more conservative treatment strategy (with lower starting dose) for older patients with mild thyroid failure than for young patients. 20 Although no differences were observed in treatment decision for vital and frail older females, treatment decisions may also depend on various patient, doctor, and healthcare characteristics (for example, age, TSH level, sex of the GP, health insurance, or medication costs). …”
Section: Comparison With Existing Literaturementioning
confidence: 93%
See 1 more Smart Citation
“…Previous studies have shown that primary hypothyroidism is associated with changes in kidney function and promotes endothelial dysfunction [20][21][22][23]. Hypothyroidism decreases renal blood flow and creatinine clearance/GFR, as reflected by an increase in creatinine levels.…”
Section: Discussionmentioning
confidence: 99%
“…Интервал 0,4-2,5 мЕд/л рядом авторов стал рассмат риваться в качестве целевого при заместительной те рапии тироксином (L Т4) [6]. Однако необходимой доказательной базой эти положения пока не подк реплены.…”
unclassified